2012
DOI: 10.1109/tasc.2012.2183843
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coil Compaction on ${\hbox {Nb}}_{3}{\hbox {Sn}}$ LARP HQ Magnet

Abstract: In the past two years the US LARP program carried out five tests on a quadrupole magnet aimed at the high luminosity upgrade of Large Hadron Collider (HiLumi-LHC). The 1-meter long, 120 mm bore Nb Sn IR quadrupole magnet (HQ) with a short sample gradient of 219 T/m at 1.9 K and a conductor peak field of 15 T is part of the US LHC Accelerator Research Program (LARP). In a series of tests, carried out at 4.4 K, the magnet reached a maximum "short-sample" performance of 86%. The tests exposed several shortcomings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…The tolerance of HQ02 and HQ03 magnets are consistent with earlier TQ quadrupole magnets developed by LARP [23]. They are higher than the positioning tolerance for the LHC NbTi magnets, typically 30 µm, because the size of Nb 3 Sn coils changes during the heat treatment [8], [25]. fabrication for HQ03 gave 10% lower positioning tolerance with respect to HQ02.…”
Section: B Coil Positioning Tolerancesupporting
confidence: 78%
See 1 more Smart Citation
“…The tolerance of HQ02 and HQ03 magnets are consistent with earlier TQ quadrupole magnets developed by LARP [23]. They are higher than the positioning tolerance for the LHC NbTi magnets, typically 30 µm, because the size of Nb 3 Sn coils changes during the heat treatment [8], [25]. fabrication for HQ03 gave 10% lower positioning tolerance with respect to HQ02.…”
Section: B Coil Positioning Tolerancesupporting
confidence: 78%
“…The alignment features at all stages of coil fabrication, magnet assembly and cold powering were incorporated first in HQ01 magnets. While the magnet reached 170 T/m, 86% of short-sample limit (SSL) at 4.4 K [6] and 184 T/m, 85% of SSL at 1.9 K [7], HQ01 magnets also revealed several issues related to the conductor damage due to coil compaction and insulation failures [8]. To address these issues, HQ02 used smaller Nb 3 Sn strands (diameter decreased from 0.8 mm to 0.778 mm) to reduce the coil compaction without significant change of the magnet fabrication tooling [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…All S2 Glass insulation is qualified by measurement at 5 MPa rather than accepting the generally oversized nominal manufacturer thickness. More extensive reductions to assumed growth increase the risk of electrical shorts during heat treatment and reduced quench performance [5], [30].…”
Section: Second Generation Mqxfmentioning
confidence: 99%
“…These models, while demonstrating operation well above the HQ target gradient of 170 T/m, were affected by stress degradation, electrical insulation failures, and large dynamic field errors [7][8][9][10]. Detailed analysis [11] led to critical revisions of the coil parameters and components which were validated through dedicated tests in a mirror structure [12][13] and gradually implemented in the HQ02 series [14]. The HQ02a model confirmed that the previous performance issues had been resolved, but its gradient was limited to 182 T/m due to the choice of a conservative pre-load level [15][16][17].…”
Section: Introductionmentioning
confidence: 99%